Biochemical and structural imaging of remodeled myocardium. Issue 28 (August 2022) - Mekkaoui, Choukri; Sosnovik, David E
Abstract : Remodeling of the myocardium results in changes in the molecular, cellular, and microstructural properties of the heart. Traditionally, these changes have been characterized using microscopy of tissue specimens taken from the heart. However, recent advances in biomedical imaging now make it possible to characterize many of these processes noninvasively. In this review, we focus on key principles and recent advances in molecular, cellular, and microstructural imaging of the heart after ischemic injury. Techniques to image cardiomyocyte death, inflammation, fibrosis, and microstructural remodeling of the heart are highlighted.